The Effect of AI Influencers in Promoting Different Levels of Brand Familiarity - Khoo, Wei Sern (Auckland University of Technology, 2025)
AI-generated influencers are an emerging technological development in the field of influencer marketing, increasingly adopted by well-known brands for endorsement campaigns. However, questions remain regarding how consumers perceive the authenticity of these influencers, especially when brand familiarity varies. This study investigates the impact of disclosing an influencer’s AI-generated identity on consumer perceptions, focusing particularly on perceived authenticity (i.e., sincerity, truthful endorsement, expertise, and naturalness), brand attitude, and purchase intention. Additionally, it examines whether brand familiarity moderates these effects. A 2×2 between-subjects experimental design was employed, manipulating (1) whether participants were told the influencer was AI-generated (told vs. not told), and (2) the brand familiarity level (high: Nike; low: Novo, a fictitious brand). A female fitness-themed AI influencer was created using Rendernet AI and featured in a sports shoe advertisement to ensure relevance to both the product category and the influencer’s domain. A total of 673 U.S.-based participants aged 19–29 were recruited via Amazon Mechanical Turk (MTurk). Data were analysed using SPSS and SmartPLS 4.0. Results showed that disclosure significantly increased perceptions that the influencer was AI-generated. In turn, perceiving the influencer as AI-generated significantly reduced perceived sincerity, truthful endorsement, expertise, and naturalness. Among these dimensions, only truthful endorsement, expertise, and naturalness had positive effects on brand attitude. Brand attitude strongly predicted purchase intention. Notably, brand familiarity alone had no direct impact on authenticity perceptions, but it marginally enhanced the perceived naturalness of AI influencers when paired with perceived AI identity, suggesting that consumers may interpret AI use by familiar brands as innovative rather than unnatural. In conclusion, this study highlights that perceived authenticity is critical to the marketing effectiveness of AI influencers. The findings contribute to the theoretical understanding of AI endorsement and offer practical guidance for brands considering AI influencers as part of their digital marketing strategy.